2019
DOI: 10.1111/soc4.12725
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood, homeschooling, and mental health

Abstract: Homeschooling fits neatly under the umbrella of intensive mothering, a prominent parenting style in the United States. Intensive mothering has been shown to increase the emotional distress of mothers, which may be exacerbated when mothers take on the additional burden of being responsible for the formal education of their children. Given that intensive mothering ideologies negatively impact maternal mental health, it makes sense to examine how homeschooling may exacerbate this outcome. In this paper, I examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
(82 reference statements)
1
14
0
Order By: Relevance
“…Our findings are in line with recent data showing that women are more likely to be taking on the role of "teacher" than men during the pandemic (Del Boca et al 2020;Miller 2020;Shafer et al 2020). Pre-pandemic evidence on voluntary homeschooling suggests that this additional burden takes a toll on the mental health of mothers (Baker 2019;Lois 2006), a finding that has been replicated in COVID-19 pandemic research (APA 2020; Schmidt et al 2020). It is concerning that greater involvement in mandatory homeschooling during the pandemic is linked with increased drinking frequency in women, given that increased drinking may interfere with the ability to parent through this challenging time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with recent data showing that women are more likely to be taking on the role of "teacher" than men during the pandemic (Del Boca et al 2020;Miller 2020;Shafer et al 2020). Pre-pandemic evidence on voluntary homeschooling suggests that this additional burden takes a toll on the mental health of mothers (Baker 2019;Lois 2006), a finding that has been replicated in COVID-19 pandemic research (APA 2020; Schmidt et al 2020). It is concerning that greater involvement in mandatory homeschooling during the pandemic is linked with increased drinking frequency in women, given that increased drinking may interfere with the ability to parent through this challenging time.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-pandemic research with families who are homeschooling on a voluntary basis supports the idea that homeschooling can be burdensome for the parent fulfilling the role of "teacher". A recent review of the voluntary homeschooling literature led authors to argue that taking on the additional role of teacher can worsen mental health issues (Baker 2019). For instance, in a qualitative study looking at the experiences of mothers who decided to homeschool, it was commonly reported that the teacher role quickly became overwhelming (Lois 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One of the frameworks employed by scholars to describe homeschooling families is ʹintensive parentingʹ (Aurini & Davies, 2005;Lois, 2012Lois, , 2017Baker, 2019) that is a frequently reified social construction according to which rearing should be ʹchild-centered, expert-guided, emotionally absorbing, labor intensive, and financially expensiveʹ (Hays, 1996:8), especially for mothers. It works as a cultural script: in the practice, it may generate different responses according to individual, gender, and cultural differences.…”
Section: Ehe: the Ideology Of Intensive Parenting And The Redefinition Of The Expertisementioning
confidence: 99%
“…Intensive parenting is frequently addressed as ʹintensive motheringʹ (Lois, 2012(Lois, , 2017Baker 2019) by the authors who stress it is a gender-specific theory originally developed by Hays (1996). Although a ʹnew model fatherʹ mirroring intensive mothering has been fostered by policymakers and experts, dominant ideologies of motherhood and fatherhood seem to remain very different (Faircloth, 2014).…”
Section: Ehe: the Ideology Of Intensive Parenting And The Redefinition Of The Expertisementioning
confidence: 99%
“…Contemporary home education has been described as the ultimate form of parental involvement in a child's education (Neuman & Aviram, 2015) and can be neatly seen as an expression of the intensive parenting ideology. Home education often entails a financial effort and, above all, emotional labour to deal with the added stress to the child-rearing ʹconventionalʹ practices and the anxiety related to the high self-expectations that the internalisation of intensive parenting produces (Baker 2019;Faircloth & Murray 2015;Lois, 2012).…”
Section: Ehe: the Ideology Of Intensive Parenting And The Redefinition Of The Expertisementioning
confidence: 99%